Developing Student Entrepreneurship Through Teaching Factory Program in the Field of Motorcycle Service - Maftukin, M; Rusdarti, Rusdarti; Anis, Samsudin (Journal of Vocational and Career Education, 2019)
Teaching Factory program in the field of motorcycle service which is developed in SMK Bina Utama Kendal is quite well. However, it does not train students to gain practical experience in applying entrepreneurship. Students have not been involved in the planning, organizing, monitoring, and evaluating stages in the teaching factory program. This research aims to develop the management model of teaching factory programs that increasing student entrepreneurship in the field of motorcycle engineering and business competence.Ã‚Â  This research use R&D methodology. The research procedure consists of (1) Introduction, (2) Developing Model, (3) Testing Model. The result of the study shows the management's last model in teaching factory program is valid, effective, and easy to use. It can be used to develop student entrepreneurship based on significant results between pretest and post-test. The model which is developed in this research use entrepreneur real concept by asking students directly and giving responsibility to start from planning, organizing, conducting, evaluating in teaching factory management. This model develops students entrepreneurship such as discipline, hard work, creativity, a sense of collaboration, honest, and goal-oriented. Furthermore, it increases student's knowledge and ability in the field of motorcycle engineering.